What Could Be the Observational Signature of Dark Matter in Globular Clusters? - Fortes, Elaine C F S; Miranda, Oswaldo D; Stecker, Floyd W; Wuensche, Carlos A (Journal of cosmology and astroparticle physics, 2020)
Here we investigate the possibility that some globular clusters (GCs) harbor intermediate mass black holes (BH) in their centers and are also embedded in a low-mass dark matter (DM) halo. Up to date, there is no evidence on whether or not GCs have DM in their constitution. For standard cold DM cosmology, it is expected that GCs form with their own DM halos. Other studies investigate the possibility that GCs were initially embedded in massive DM halos that evolved during the cluster lifetime. An additional intriguing question is related to the existence of intermediate mass black holes (IMBH) in the GCs. The determination of whether GCs hold IMBHs would be able to answer important questions about GCs formation and the circumstances that gave rise to the IMBHs. DM & IMBH in the context of GCs are interesting subjects to be studied and we will perform such studies here, assuming the coexistence of both of them in some GCs. Having such information, we perform the study possible DM signals from GCs. One important subject to be studied is the DM density profile. In the inner regions of GCs, the DM density profile is still an open question of fundamental importance to DM studies, specially for the study of radio and γ-ray emission from DM annihilation in such regions. Here we consider the case of IMBHs in the inner regions of three GCs: 47 Tuc, NGC 6266 and ω Cen. The existence of a black hole (BH) directly affects the matter distribution in its vicinity. These effects are significant for IMBHs as well as supermassive black holes (SMBHs) and can lead to large DM overdensities called spikes. In this paper, we direct our studies to the radio synchrotron emission from DM annihilation with spike profiles around possible IMBHs in GCs. We present our results for synchrotron emission produced by DM annihilation via bbar b channel. We use the best-fit DM mass of 34 GeV and annihilation channel in bbar b used to explain the Galactic center "excess" and perform our analysis for the estimated radio flux. We direct our attention specially to the γ-ray emission from 47 Tuc. When considering a scenario wich includes a BH and the combined analysis of multi-wavelength studies, we conclude that some parameter choice as the annihilation cross section ⟨σ v⟩ used to fit the γ-ray excess differs by many orders of magnitude from the one necessary to fit the radio observations for this globular cluster if we consider the BH scenario.